Resilience in Aging Concepts, Research, and Outcomes (Springer International Publishing, 2018)
This updated and expanded second edition of Resilience in Aging offers a comprehensive description of the current state of knowledge with regard to resilience from physiological (including genetic), psychological (including cognitive and creative), cultural, and economic perspectives. In addition, the book considers the impact of resilience on many critical aspects of life for older adults including policy issues, economic, cognitive and physiological challenges, spirituality, chronic illness, and motivation. The only book devoted solely to the importance and development of resilience in quality of life among older adults, Resilience in Aging, 2nd Edition continues to offer evidence-based theory, clinical guidelines, and new and updated case examples and real-world interventions so professional readers can make the best use of this powerful tool. The critical insights in this volume are concluded with a discussion of future directions on optimizing resilience and the importance of a lifespan approach to the critical component of aging. The book's coverage extends across disciplines and domains, including: Resilience and personality disorders in older age. Cultural and ethnic perspectives on enhancing resilience in aging Sustained by the sacred: religious and spiritual factors for resilience in adulthood and aging. Building resilience in persons with early-stage dementia and their care partners. Interdisciplinary geriatric mental health resilience interventions. Developing resilience in the aged and dementia care workforce. Using technology to enhance resilience among older adults. This wide-ranging and updated lifespan approach gives Resilience in Aging, 2nd Edition particular relevance to the gamut of practitioners in gerontology and geriatrics, including health psychologists, neuropsychologists, clinical psychologists, psychiatrists, social workers, geriatricians, family physicians, nurses, occupational and physical therapists, among others.